2015
DOI: 10.1371/journal.pone.0120083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phthalates on Cytokine Production in Monocytes and Macrophages: A Systematic Review of Experimental Trials

Abstract: BackgroundPhthalates are a group of endocrine disrupting chemicals suspected to influence the immune system. The aim of this systematic review is to summarise the present knowledge on the influence of phthalates on monocyte and macrophage production and secretion of cytokines, an influence which could affect both pro- and anti-inflammatory abilities of these cells.Strategy and ResultsA systematic search was performed in Medline, Embase and Toxline in June 2013, last updated 3rd of August 2014. Criteria used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 69 publications
(167 reference statements)
0
21
0
Order By: Relevance
“…The study by Greene et al reported that Di-(2-ethylhexyl)phthalate (DEHP) may act directly on Mɸs increasing chemokine and cytokine gene expression altering their responses, and in women may drive alteration of uterine and/or MΦ factors involved in develop of endometriosis [ 149 ]. Studies that have investigated the influence of phthalates on cytokine secretion by primary human peripheral blood mononuclear cells (MNC) and lymphocytes T showed that phthalate diesters influence cellular signal pathways that lead cytokine production, enhancing the secretion of interleukin (IL)-6, IL-10 and the chemokine CXCL8 and impairing release of tumor necrosis factor (TNF)-α, IL-2, IL-4, and interferon-γ [ 150 ], which could hypothetically prime a decreased synthesis of antibodies, albeit impact of phthalates on cytokine expression was nor confirmed in other studies [ 143 , 151 ]. Other immune parameters, such as weight of lymphoid organs, thymus histology, and antibody levels were evaluated and no effects [ 151 ] or immunosuppression were observed [ 152 ].…”
Section: Toxicological Aspects and Human Health Effectsmentioning
confidence: 99%
“…The study by Greene et al reported that Di-(2-ethylhexyl)phthalate (DEHP) may act directly on Mɸs increasing chemokine and cytokine gene expression altering their responses, and in women may drive alteration of uterine and/or MΦ factors involved in develop of endometriosis [ 149 ]. Studies that have investigated the influence of phthalates on cytokine secretion by primary human peripheral blood mononuclear cells (MNC) and lymphocytes T showed that phthalate diesters influence cellular signal pathways that lead cytokine production, enhancing the secretion of interleukin (IL)-6, IL-10 and the chemokine CXCL8 and impairing release of tumor necrosis factor (TNF)-α, IL-2, IL-4, and interferon-γ [ 150 ], which could hypothetically prime a decreased synthesis of antibodies, albeit impact of phthalates on cytokine expression was nor confirmed in other studies [ 143 , 151 ]. Other immune parameters, such as weight of lymphoid organs, thymus histology, and antibody levels were evaluated and no effects [ 151 ] or immunosuppression were observed [ 152 ].…”
Section: Toxicological Aspects and Human Health Effectsmentioning
confidence: 99%
“…Due to its higher production and application figures, PAEs are widely distributed in various environmental samples such as the air [11], freshwater [12,13], sediment [14,15] and soil [5,[16][17][18]. Several studies have reported that PAEs can cause negative health effects in animals [19,20] and humans [21][22][23]. Therefore, the United States Environmental Protection Agency (USEPA) and government agencies in several other countries have categorized six PAEs as priority environmental pollutants and as endocrine-disrupting compounds (EDCs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…During the inflammatory condition, monocytes/macrophages activated by various stimulants can secrete inflammatory cytokines, such as TNF-α, IL-1β, IL-6, IL-10, and IL-18 20 . To determine whether the 2 miRs encapsulated in EMPs can modulate the expression level of inflammatory cytokines in monocytes/macrophages, we transfected the 2 miRs into the THP-1 monocytes.…”
Section: Resultsmentioning
confidence: 99%